Pengaruh Motivasi Terhadap Prestasi Belajar Mata Pelajaran Fiqih Siswa Kelas XI MA Roudlotul Muta’allimin Simbar Tampo Cluring Banyuwangi Tahun Pelajaran 2015/2016 - Al Rosid, Moh. Harun (IAI Darussalam, 2017)
The purpose of this study to determine the motivation of learning subjects fiqih class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi 2015/2016 year. To know the learning achievement of fiqih subjects of class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi 2015/2016. To know the effect of motivation on the achievement of learning subjects fiqih class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi academic year 2015/2016. This research uses quantitative method with product moment technique. Conclusion 1) Based on the t test obtained the results of student learning motivation (X) variable is fairly good; 2) Based on the t test obtained the results of student learning achievement (Y) variable is fairly good; 3) Based on the calculations performed by using a simple regression formula t arithmetic significant influence with regression coefficient of 0.140 which is pentropped to 14%. Thus there is influence of learning motivation to learning achievement equal to 14%.